PENGARUH ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) DISCLOSURE TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN TAMBANG YANG TERDAFTAR DI BEI PERIODE 2016-2022) - Manal Safana, Nyimas; Dharma, Fitra; Retno Yuni Nur Susilowati (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This research is designed to assess the influence of Environmental, Social, and Governance (ESG) reporting transparency on enterprise value among mining companies listed on the IDX between 2016 and 2022. The study employs Environmental Disclosure, Social Disclosure, and Governance Disclosure as independent constructs, while enterprise value is designated as the dependent construct, measured via the Price-to-Book Value (PBV) ratio. Moreover, firm size and profitability, quantified through Return on Equity (ROE), are utilized as control elements. The findings reveal that Governance Disclosure maintains a statistically significant positive relationship with enterprise value, indicating that comprehensive governance frameworks can cultivate investor trust and generate superior market evaluations. Conversely, Environmental and Social Disclosures show no meaningful impact on corporate valuation. These discoveries highlight the fundamental importance of governance in enhancing organizational performance from investors' standpoint. The study emphasizes the critical requirement for companies to strengthen their sustainability reporting mechanisms, particularly in sectors that demonstrate stronger correlations with investor attitudes and market recognition, thereby facilitating more effective stakeholder satisfaction.